Daylight metrics and requirements : a review of reference documents for architectural practice - Pinheiro, Amanda Moura (2024)
Daylight has always been part of the architectural practice, since architects always used it to define spaces and create complex structures. Daylighting is, nowadays, seen as key strategy for sustainability, energy efficiency and resilience in buildings. This article aims to investigate daylight requirements in reference documents for architectural practice, through the collection and qualitative analysis of documents. To the analysis, primary documents were collected through active searches and through the application of a survey to daylight specialists from different countries. Then, 130 reference documents were analysed, divided into standards, rating systems, building and urban codes, regulations and guidelines. Results show that static and dynamic metrics are common within standards and rating systems, while building and urban codes and regulations often use metrics based on building and urban geometry. Among standards and rating systems, Daylight Factor (DF) is still one of the most used metrics, even if dynamic metrics offer advanced analyses; building and urban codes and regulations are very specific from each location, with predominant use of geometric metrics; and guidelines can use both types of metrics.